Bilingual Website and E-Catalogue to Support Micro Small Medium Enterprises Handmade Woven Bag - Aprilia Tri Anggraeni; Mariana Ulfah Hoesny (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Tas Anyaman Mba Ratna, an MSME in Kediri Regency, has strong local and international market potential but faces challenges due to limited digital knowledge and resources. To address this, a bilingual website and e-catalogue (Indonesian-English) were developed to enhance market reach and product visibility. The development process began with needs analysis through social media observation and interviews with the owners. Based on this, an attractive and responsive design was created, integrated with social media and marketplaces. The final platform features a business profile, product catalogue, gallery, and contact details in two languages. Evaluation by 30 potential users showed high satisfaction, with a 4.67 average score (93.48%), highlighting ease of access, informativeness, and appealing design. Suggestions included adding more product variations and enhancing e-commerce functions. Overall, this digital tool effectively supports Tas Anyaman Mba Ratna in expanding their market and competing globally.